Abscisic acid‐mediated modifications of radial apoplastic transport pathway play a key role in cadmium uptake in hyperaccumulator Sedum alfredii. (19th January 2019) - Tao, Qi; Jupa, Radek; Liu, Yuankun; Luo, Jipeng; Li, Jinxing; Kováč, Ján; Li, Bing; Li, Qiquan; Wu, Keren; Liang, Yongchao; Lux, Alexander; Wang, Changquan; et al.
Abstract: Abscisic acid (ABA) is a key phytohormone underlying plant resistance to toxic metals. However, regulatory effects of ABA on apoplastic transport in roots and consequences for uptake of metal ions are poorly understood. Here, we demonstrate how ABA regulates development of apoplastic barriers in roots of two ecotypes of Sedum alfredii and assess effects on cadmium (Cd) uptake. Under Cd treatment, increased endogenous ABA level was detected in roots of nonhyperaccumulating ecotype (NHE) due to up‐regulated expressions of ABA biosynthesis genes ( SaABA2, SaNCED ), but no change was observed in hyperaccumulating ecotype (HE). Simultaneously, endodermal Casparian strips (CSs) and suberin lamellae (SL) were deposited closer to root tips of NHE compared with HE. Interestingly, the vessel‐to‐CSs overlap was identified as an ABA‐driven anatomical trait. Results of correlation analyses and exogenous applications of ABA/Abamine indicate that ABA regulates development of both types of apoplastic barriers through promoting activities of phenylalanine ammonialyase, peroxidase, and expressions of suberin‐related genes ( SaCYP86A1, SaGPAT5, and SaKCS20 ). Using scanning ion‐selected electrode technique and PTS tracer confirmed that ABA‐promoted deposition of CSs and SL significantly reduced Cd entrance into root stele. Therefore, maintenance of low ABA levels in HE minimized deposition of apoplastic barriers and allowed maximization of Cd uptake via apoplastic pathway. Abstract : Abscisic acid regulated the development of endodermal Casparian strips (CSs) and suberin lamellae (SL) in roots of S. alfredii exposed to Cd. Maintenance of low ABA levels in hyperaccumulating ecotype minimized deposition of CSs/SL and allowed maximization of Cd uptake via apoplastic pathway.